Cubital tunnel syndrome due to an elbow injury. Case report - Leila A. Edilgireeva; Mikhail G. Bashlachev; Inna Ya. Malsagova; Hayder N. Akif (Consilium Medicum, 2024)
Cubital tunnel syndrome is a symptomatic dysfunction of the ulnar nerve, resulting from compression of the nerve within the walls of the tunnel. This condition causes irreversible sensory disturbances, muscle weakness in the hand, trophic disorders, and the formation of secondary contractures. There is temporary loss of ability to work. Therefore, the issues of surgical interventions before the appearance of symptoms are important. The article presents an observation of a 35-year-old male with compression ischemic neuropathy of the ulnar nerve at the cubital tunnel level. Microsurgical decompression of the left ulnar nerve at the cubital tunnel level and neurotization of the motor portion led to a complete regression of pain, motor disorders, sensory disturbances and a significant improvement in functional condition. The issues of diagnosis, conservative and surgical treatment of cubital tunnel syndrome are discussed.